Establishing a Moderate Religious Academics in Pesantren-Based Higher Education - Ahmad Royani (Cendekia: Kependidikan dan Kemasyarakatan, 2021)
Abstract: Pesantren is an ideal partner for the government to jointly improve the quality of education as a basis for implementing social transformation. It provides qualified human resources with good morals emphasizing moderate religious values that reflect within the Islamic value of rahmatan lilalamin. This paper wants to see pesantren-based universities in giving birth to moderate religious academics. By taking the object of study Nurul Jadid university, which is a high miscarriage based pesantren. This research applied a descriptive study by using a qualitative approach. The research participants were Islamic scholars (kyai), lecturers, and students at the University of Nurul Jadid. Data were collected through interviews, observation, and documentation. This study showed that establishing the Islamic boarding school culture produced moderate religious academics at Nurul Jadid University. It was by implementing the supremacy of kyai’s preaching and teaching (dawuh kyai). It was constructed through artifacts, values, and assumptions emphasizing moderate religious aspects. Abstrak: Pesantren menjadi partner yang ideal bagi pemerintah untuk bersama-sama meningkatkan mutu pendidikan sebagai basis bagi pelaksanaan transformasi sosial melalui penyediaan sumber daya manusia yang mumpuni dan berakhlakul karimah yang menekankan nilai-nilai religius moderat yang mencerminkan nilai Islam rahmatan lilalamin. Tulisan ini ingin melihat perguruan tinggi berbasis pesantren dalam melahirkan akademisi religius moderat. Dengan mengambil objek kajian Universitas Nurul Jadid yang merupakan perguran tinggi berbasis pesantren. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi kasus. Teknik pengumpulan data menggunakan wawancara mendalam,observasi partisipatif dan studi dokumen. Data-data yang yang terkumpul kemudian dianalisis secara simultan, dengan teknik: pengumpulan data, kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menemukan konstruksi budaya pesantren dalam melahirkan akademisi religius moderat di Univesitas Nurul Jadid dilakukan dengan kekuatan dawuh kyai yang di konstruksi melalui artifak, nilai, dan asumsi yang mengedepankan aspek religius moderat